STUDY OF PHRASEOLOGICAL UNITS IN OTHER LANGUAGES - Shadmanov Sherzod Khursanaliyevich; Shadmanova Nozima Bakhodirovna (Galaxy International Interdisciplinary Research Journal, 2022)
Phraseology is a very complex phenomenon, the study of which requires specific study methods and also requires the use of such disciplines as lexicology, grammar, stylistics, phonetics, language history, logic, and local studies.